2015
DOI: 10.2174/1874613601509010051
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Cardiovascular Diseases in HIV/AIDS Patients on HAART

Abstract: Background : The introduction and widespread use of combination antiretroviral therapy referred to as highly active antiretroviral therapy (HAART) in the mid 1990’s, has led HIV-infected individuals to experience a dramatic decline in immunodeficiency-related events and death. There is growing concern on metabolic complications associated with HIV and HAART which may increase cardiovascular risk and disease. The aim of this study was to investigate the cardiovascular risk profile of HIV/AIDS patients receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 37 publications
(43 reference statements)
10
54
1
2
Order By: Relevance
“…After screening, 20 articles met the eligibility criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and were included in the analysis (figure 1). Of these, seven 17-23 articles reported incidence of T2DM in HIV-infected participants, eight 24-31 reported prevalence of T2DM in HIV-infected participants compared with uninfected controls and five 32-36 reported prevalence of T2DM in HIV-infected participants on treatment compared with untreated controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 20 articles met the eligibility criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and were included in the analysis (figure 1). Of these, seven 17-23 articles reported incidence of T2DM in HIV-infected participants, eight 24-31 reported prevalence of T2DM in HIV-infected participants compared with uninfected controls and five 32-36 reported prevalence of T2DM in HIV-infected participants on treatment compared with untreated controls.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows the data for five studies included in the meta-analysis comparing HIV treated (n=1120) with untreated participants (n=828). The majority of included participants were women (ranged from 58% 34 to 75% women 36 figure 5.…”
Section: Incidence Of T2dm In Hiv-infected Participantsmentioning
confidence: 99%
“…Indeed, an increase in oxidative stress has been frequently associated with antiretroviral treatment in HIV patients [128-130]. Several studies have demonstrated that the increase in ROS production mediated by HAART favours the onset of ageing-associated diseases [131-133]. Moreover, accumulation of somatic mutations in mtDNA and ROS in hematopoietic progenitors may account for the persistence of immune dysfunction observed after therapy withdrawal [8].…”
Section: Art and Mitochondriamentioning
confidence: 99%
“…En un estudio realizado por Mashinya y Colaboradores donde evaluaron los efectos adversos de la TAR, perfil lipídico, tabaquismo, obesidad, diabetes, carga viral y conteo de CD4, concluyeron que los factores de riesgo cardiovasculares fueron frecuentes en la población infectada con VIH en tratamiento y además una alta proporción de estos se encontraban en moderadoalto riesgo según la escala Framinghan 13,20 . Otro estudio realizado por Dickson y Colaboradores cuyo objetivo era investigar el perfil de riesgo cardiovascular de los pacientes VIH que recibían TARGA y de los que no la recibían, el resultado obtenido asoció el tratamiento de la TARGA con mayor prevalencia de hipercolesterolemia, aumento de colesterol LDL e hipertensión arterial 21 . coMproMIso cardIovascular en pacIentes con vIH…”
Section: Fisiopatologíaunclassified